PREEMPTIVE VASCULAR ACCESS IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Jeamanukoolkit, Paiboon (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
The incidence of chronic kidney disease (CKD) in patients who need renal replacement therapy (RRT) in the Thai population is high. There are three choices for RRT, among them, hemodialysis is good and the most popular. There is a recommendation from the KDOQI 2006 guideline that CKD patients with less than 30 mL/min/1.73 m2 (CKD stage IV) should be referred to a vascular surgeon for patient education and preparation for RRT with preemptive vascular access. Current problems are found in the importance of preemptive hemodialysis access in CKD patients is less common, so the patients often experienced of catheter insertion for hemodialysis. This short review article reflects the importance of preemptive vascular access in ESRD patients. They should collaborate on a long-term plan for RRT with their physicians and attain sufficient knowledge and quality of life with the process of hemodialysis.